Comparative study between two days versus seven days urethral stenting of distal hypospadias after tubularized incised plate urethroplasty - Fakhry, Tamer; Amer, Ahmed Mohammad; Fawzy, Ahmed Nabil (International Surgery Journal, 2021)
Background: The duration of urethral stenting after tubularized incised plate (TIP) urethroplasty for hypospadias varies among surgeons. Methods: Forty male cases with distal hypospadias aging from one year till the age of six years randomly allocated into two groups for undergoing tubularized incised plate urethroplasty with removal of the urethral stent after two days in one group and after seven days in the other one. The rate of postoperative complications such as urethrocutaneous fistula, urinary retention, meatal stenosis and complete wound dehiscence requiring redo and cosmetic results were compared. Results: The prevalence of post-operative complications and cosmetic results in two studied groups were not significantly different. Conclusions: There is no significant difference between removal of the stent after two days or seven days regarding the incidence of postoperative complications and the cosmetic results.